The Smart Medication Vest / Nur Farhana Abdul Samat … [et al.] - ABDUL SAMAT, NUR FARHANA; ABD RAHMAN, ROSENAH; SHAMSUDIN, SHAHIDA; CHE MOHAMED SUKRI, SITI NAFISAH; ABDUL GANI, SITI NORFAHANA (2018)
From the statistic of incident medication error in the ward and from the team's experience as nurses in medication administration, the team had chosen a product that we believe can reduce and preventing the incident of medication error among the nurses in the hospital. The product is The Smart Medication Vest. One of the causes of incident medication error occur is the nurses have been distracted and interrupted during the medication administration process. This product is suitable to lessen the interruption while serving medication.